An Application of the Core and Balance Model of Family Leisure Functioning to Study Leisure Activities Practised by Families from Wielkopolska - Beata Pluta (Studia Periegetica)
The purpose of this study was to examine family leisure involvement in 60 Polish families from Wielkopolska from the perspective of parents and their children. The Core and Balance Model of Family Leisure Functioning (CBM) was used to examine the relationship between core and balance activities and the level of satisfaction with family leisure involvement. Two questionnaires were used: the Family Leisure Activity Profile (FLAP) and the Family Leisure Satisfaction Scale (FLSS). The families in the sample were found to take part in core activities more frequently. While the level of involvement in family leisure was average, the level of satisfaction derived from it was relatively high. The findings indicate that the Polish version of the FLAP can be a useful tool in the study of leisure behaviour of Polish families.